Penggunaan Media Flash Card dalam Meningkatkan Literasi di Sekolah Dasar Katolik Lamabelawa - Yohanes Klimaks Paskalis Barung; Kristianus Simon Hale Molan; Yasinta Palan Peten (Universitas Kristen Indonesia Toraja, 2024)
Literacy is the ability of learners to process and understand information when learners carry out the process of reading and writing. Lamabelawa Village in Witihama sub-district, East Flores district. This village is one of the villages chosen to carry out Merdeka Learning Campus activities, in collaboration with the Faculty of Social and Political Sciences, Widya Mandira Catholic University. Based on observations, it turns out that there is very little about the importance of literacy and about how to do learning using flash card media, so the developer uses the direct method of learning in order to build a good relationship with students. The purpose of the activity is to help students develop a better understanding delivered through image media, and enrich their understanding visually. This program started from April to June 2024. The number of students involved in the activity amounted to 12 first grade elementary school students. After evaluating the flash card media, the students became more active and easy to interact with the students. Improving Literacy at Lamabelawa Catholic Elementary School